Immunoglobulin replacement in hematological malignancies: a focus on evidence, alternatives, dosing strategy, and cessation rule. Issue 1 (2nd January 2023) - Sim, Beatrice; Ng, Jun Yen; Teh, Benjamin W.; Talaulikar, Dipti
Abstract: Acquired hypogammaglobulinemia or secondary immunodeficiency (SID) occurs commonly in hematological malignancies with increasing incidence and complexity in the era of modern therapies. Despite current practice of immunoglobulin replacement (IgRT) in SID, the evidence is lacking, especially for newer treatments. We discuss the current evidence for IgRT in various disease groups including issues, such as actual or ideal body weight (IBW)-based dosing, length of treatment, antibiotic prophylaxis, and vaccination. Incidence of SID with newer treatment is lacking. While there is a trend toward decreased respiratory infections and hospitalizations with IgRT, this is not consistent across all disease course or treatment groups. Dosing and indications for cessation of IgRT are also inadequately characterized. Further randomized controlled trials (RCTs) and observational studies are required to assess the optimal indications, timing, and duration of IgRT to improve the efficacy, safety, and cost-effectiveness. Assessment of alternative and adjunctive therapies, such as vaccination and antibiotic prophylaxis could also improve the outcomes and costs.